Targeting super-enhancer-associated oncogenes in oesophageal squamous cell carcinoma. Issue 8 (10th May 2016) - Jiang, Yan-Yi; Lin, De-Chen; Mayakonda, Anand; Hazawa, Masaharu; Ding, Ling-Wen; Chien, Wen-Wen; Xu, Liang; Chen, Ye; Xiao, Jin-Fen; Senapedis, William; Baloglu, Erkan; Kanojia, Deepika; et al.
Abstract : Objectives: Oesophageal squamous cell carcinoma (OSCC) is an aggressive malignancy and the major histological subtype of oesophageal cancer. Although recent large-scale genomic analysis has improved the description of the genetic abnormalities of OSCC, few targetable genomic lesions have been identified, and no molecular therapy is available. This study aims to identify druggable candidates in this tumour. Design: High-throughput small-molecule inhibitor screening was performed to identify potent anti-OSCC compounds. Whole-transcriptome sequencing (RNA-Seq) and chromatin immunoprecipitation sequencing (ChIP-Seq) were conducted to decipher the mechanisms of action of CDK7 inhibition in OSCC. A variety of in vitro and in vivo cellular assays were performed to determine the effects of candidate genes on OSCC malignant phenotypes. Results: The unbiased high-throughput small-molecule inhibitor screening led us to discover a highly potent anti-OSCC compound, THZ1, a specific CDK7 inhibitor. RNA-Seq revealed that low-dose THZ1 treatment caused selective inhibition of a number of oncogenic transcripts. Notably, further characterisation of the genomic features of these THZ1-sensitive transcripts demonstrated that they were frequently associated with super-enhancer (SE). Moreover, SE analysis alone uncovered many OSCC lineage-specific master regulators. Finally, integrative analysis of both THZ1-sensitive and SE-associated transcripts identified a number of novel OSCC oncogenes, including PAK4, RUNX1, DNAJB1, SREBF2 and YAP1, with PAK4 being a potential druggable kinase. Conclusions: Our integrative approaches led to a catalogue of SE-associated master regulators and oncogenic transcripts, which may significantly promote both the understanding of OSCC biology and the development of more innovative therapies.